STRATEGI PUBLIC RELATION DALAM UPAYA MENJAGA CITRA DESTINASI WISATA DI MUSEUM NASIONAL INDONESIA - Dewi, Nadya Cantika; Putra, Gilang Pratama; Rohaeni, Neni (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2024)
In the current era of digitalization, social media is a digital platform that has an important role in marketing. This thesis aims to analyze the strategies owned by the National Museum through the role of public relations in digital marketing activities as an effort to maintain the image of tourist destinations that are in the process of repair or revitalization. This research uses qualitative methods and obtains data with observation techniques and interview instruments conducted with the National Museum of Indonesia. The results obtained show that there is an influence felt by the management of the public relations strategy, and get a positive response and view from the community. Through this research, public enthusiasm for the museum can be seen through comments made by the public on digital uploads of images or videos by the museum on digital platforms. From this research, it is hoped that the positive views that the community already has towards the museum must be maintained and improved, this is also part of digital marketing as a way to improve the quality and number of tourist visitors.